Numerical Analysis of Coupled Thermal-Mechanical on Drum Brakes - Hukmanul Fikri; Delima Yanti Sari; Waskito Waskito; Wanda Afnison (Jurnal Vokasi Mekanika (VoMek), 2025)
Drum brakes are one of the crucial components in motor vehicle braking systems, particularly in motorcycles, due to their advantages in production cost and resistance to environmental contamination. However, this type of brake has limitations in dissipating heat during braking, which can lead to temperature accumulation, thermal deformation, and reduced braking efficiency. This study aims to analyze the thermo-mechanical performance of drum brakes with various cooling groove designs (solid, straight-grooved, and slant-grooved) using a numerical method based on Finite Element Analysis (FEA) in ANSYS Workbench. The analysis was conducted in a transient manner, both thermally and structurally, to evaluate temperature distribution and total deformation for each design. The results show that the slant-grooved drum brake design yields the lowest temperature distribution and total deformation values, especially at high braking speeds, with a temperature distribution of 56.899?°C and total deformation of 17.67?×?10?³?mm. These findings indicate that groove design significantly affects the heat dissipation and structural deformation performance of the brake system. The study concludes that the slant-grooved design is superior in reducing heat and deformation, thereby offering the potential to improve braking safety and efficiency.